Living with the Genome. Ethical and Social Aspects of Human Genetics - Angus Clarke [ editor ] (Palgrave Macmillan, 2006)
This book brings us up to date with important contributions from the authoritative Encyclopedia of the Human Genome on the ethical, legal and social aspects of the genome enterprise.